2021
DOI: 10.1007/s43188-021-00096-z
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 1-aminopyrene level in Koreans as a biomarker for the amount of exposure to atmospheric 1-nitropyrene

Abstract: Abstract1-Nitropyrene (1-NP) is a major nitro-polycyclic aromatic hydrocarbon (nitro-PAH), and a common constituent in diesel exhaust particles (DEPs). Absorbed 1-nitropyrene is partly metabolized to 1-aminopyrene and excreted in urine. Recently, the number of diesel cars has been increasing, which could be a major cause of air pollution, resulting elevated levels of traffic-related DEPs around cities. The aim of this study was to investigate the usability of 1-aminopyrene (1-AP) as a biomarker for DEP exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, urinary concentration of 1-NAAP, another 1-NP metabolite, was significantly associated with 8-OHdG urinary concentration. In the human body, absorbed 1-NP is mostly metabolized to 6-OHNP, 8-OHNP, or 3-OHNP, and less than 10%, on average, is metabolized to 1-AP or 1-NAAP [ 32 , 33 ]. These results suggest that 8-OHdG is produced when 1-NP is metabolized to 1-AP or 1-NAAP but not when 1-NP is metabolized to 6-OHNP [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, urinary concentration of 1-NAAP, another 1-NP metabolite, was significantly associated with 8-OHdG urinary concentration. In the human body, absorbed 1-NP is mostly metabolized to 6-OHNP, 8-OHNP, or 3-OHNP, and less than 10%, on average, is metabolized to 1-AP or 1-NAAP [ 32 , 33 ]. These results suggest that 8-OHdG is produced when 1-NP is metabolized to 1-AP or 1-NAAP but not when 1-NP is metabolized to 6-OHNP [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…148 Moreover, a previous study leveraged the amino acid metabolite of 1-NP, 1-aminopyrene, transformed from the nitro-reduction reaction, as a biomarker to assess atmospheric exposure to 1-NP. 143 Furthermore, in a distinct study involving 82 male workers in the U.S. trucking industry, Neophytou et al used urinary concentrations of biotransformation metabolites of 1-nitronaphthalene and 2nitronaphthalene, specifically 1-aminonaphthalene and 2aminonaphthalene, as potential biomarkers for traffic-related occupational exposure. The detected levels of these metabolites were observed to be associated with the presence of urinary 8-hydroxy-2-deoxyguanosine (8-OHdG), a biomarker of oxidative DNA damage, suggesting a potential correlation between NPAHs exposure and oxidative stress.…”
Section: Derivatives and Potential Exposure Biomarkersmentioning
confidence: 99%
“…Given its abundance and substantial contribution to the mutagenicity of diesel exhaust particles, 1-NP and its biomarkers, derived from hydroxylation and oxidation reactions, such as hydroxy-1-nitropyrenes and hydroxy- N -acetyl-1-aminopyrenes, have been employed as biomarkers to assess diesel exhaust exposure. , 2-Aminofluorene, another amino acid metabolite of NPAHs, has also been identified as a biomarker of DE exposure in urban residents . Moreover, a previous study leveraged the amino acid metabolite of 1-NP, 1-aminopyrene, transformed from the nitro-reduction reaction, as a biomarker to assess atmospheric exposure to 1-NP . Furthermore, in a distinct study involving 82 male workers in the U.S. trucking industry, Neophytou et al used urinary concentrations of biotransformation metabolites of 1-nitronaphthalene and 2-nitronaphthalene, specifically 1-aminonaphthalene and 2-aminonaphthalene, as potential biomarkers for traffic-related occupational exposure.…”
Section: Biotransformation Routes Of Pah Derivatives and Potential Ex...mentioning
confidence: 99%
“…There is a study had measured the indoor PAH concentration of rural households in China found that the kitchen in winter has a high PAH concentration, which is harmful to the health of people cooking in the family . The concentration of 1-aminopyrene detected in urine samples of workers working on vehicle roads or bus terminals is significantly related to the concentration of 1-nitropyrene in the atmosphere, which suggests that humans are exposed to PAHs through inhalation …”
Section: Pathways Of Human and Animal Exposure To Pah Derivativesmentioning
confidence: 99%